1993
DOI: 10.3171/jns.1993.78.1.0032
|View full text |Cite
|
Sign up to set email alerts
|

Odontoid fractures in elderly patients

Abstract: This retrospective analysis describes the clinical characteristics, treatment, and outcome of 19 patients aged 80 years or older with odontoid fractures. The fractures were due to falls in 15 patients (78.9%) and were associated with motor-vehicle accidents in four. Type III fractures were seen in three patients and type II fractures in 16. No patient suffered a neurological injury associated with the fracture. Five patients (26.3%) died during hospitalization; factors contributing to their death included prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
2
12

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(171 citation statements)
references
References 27 publications
4
153
2
12
Order By: Relevance
“…In contrast to previous studies dealing with this clinically relevant topic [1,6,9,10,15,31,64], all patients included in this study were subject to not only pre-but also postoperative CT-scans, providing valuable data regarding fracture properties and factors influencing osseous union rates. Our findings confirmed that AOSF in the recent reducible OF represents a safe alternative to posterior fusion in the appropriately selected elderly patient and fracture.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous studies dealing with this clinically relevant topic [1,6,9,10,15,31,64], all patients included in this study were subject to not only pre-but also postoperative CT-scans, providing valuable data regarding fracture properties and factors influencing osseous union rates. Our findings confirmed that AOSF in the recent reducible OF represents a safe alternative to posterior fusion in the appropriately selected elderly patient and fracture.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of patients' age at index surgery on outcome was discussed controversially. While it was shown to have significant impact on union rates in several studies [6][7][8][9][10]30], other authors did not find a significant correlation between age and union rates [15,18,20,31]. Besides age, the number of screws used for AOSF might have significant impact on union rates, too.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no single universally accepted method of management of these fractures [11,25]. Nonoperative treatment with a rigid brace can result in fracture healing without need for surgery [5], but a mortality rate of 26% to 47% in elderly patients has been reported, perhaps as a result of respiratory-related complications due to prolonged external immobilization [7,23,31,35]. Reported healing after external immobilization has varied widely from 7% to 100% [26][27][28].…”
Section: Introductionmentioning
confidence: 99%